Analisis Perbandingan Kinerja Keuangan Periode 2018-2022 pada Bank BTPN Syariah dan Bank Bukopin Syariah - Ahmad Fauzul Hakim Hasibuan; Nugra Kurnianto; Malikud Dhahir; Fajar Iqbal (Fakultas Ekonomi dan Bisnis Islam, 2023)
The Objective Of This Study Is To Empirically Investigate And Demonstrate The Differences In Financial Performance Between Bank BTPN Syariah And Bank BUKOPIN Syariah During The Period 2018-2022. The Research Employs A Comparative Descriptive Method And Collects Secondary Data In The Form Of Financial Statements From Bank BTPN Syariah And Bank BUKOPIN Syariah, Obtained From The Financial Reports Published By Bank Indonesia Through The Respective Banks' Official Websites. Data Analysis Is Conducted Using Financial Ratios Such As CAR (Capital Adequacy Ratio), ROA (Return On Assets), ROE (Return On Equity), FDR (Loan To Deposit Ratio), And NPF (Non-Performing Financing). The Analysis Method Employed Compares The Financial Performance Of Bank BTPN Syariah And Bank BUKOPIN Syariah. The Analysis Results Indicate That Overall, Bank BTPN Syariah Exhibits Better Financial Performance Compared To Bank BUKOPIN Syariah In Terms Of Capital, Profitability, Efficiency, Liquidity, And Quality Of Non-Performing Financing. This Study Provides Insights Into The Differences In Financial Performance Between Bank BTPN Syariah And Bank BUKOPIN Syariah During The Period 2018-2022. However, It Should Be Noted That This Study Has Limitations, And Other Factors That Were Not Considered May Influence The Financial Performance Of Each Bank Keywords: CAR, ROA, ROE, FDR, NPF.